How should community health workers in fragile contexts be supported: qualitative evidence from Sierra Leone, Liberia and Democratic Republic of Congo - Joanna Raven; Haja Wurie; Ayesha Idriss; Abdulai Jawo Bah; Amuda Baba; Gartee Nallo; Karsor K. Kollie; Laura Dean; Rosie Steege; Tim Martineau; Sally Theobald (BMC, 2020)
Abstract Background Community health workers (CHWs) are critical players in fragile settings, where staff shortages are particularly acute, health indicators are poor and progress towards Universal Health Coverage is slow. Like other health workers, CHWs need support to contribute effectively to health programmes and promote health equity. Yet the evidence base of what kind of support works best is weak. We present evidence from three fragile settings-Sierra Leone, Liberia and Democratic Republic of Congo on managing CHWs, and synthesise recommendations for best approaches to support this critical cadre. Methods We used a qualitative study design to explore how CHWs are managed, the challenges they face and potential solutions. We conducted interviews with decision makers and managers (n = 37), life history interviews with CHWs (n = 15) and reviewed policy documents. Results Fragility disrupts education of community members so that they may not have the literacy levels required for the CHW role. This has implications for the selection, role, training and performance of CHWs. Policy preferences about selection need discussion at the community level, so that they reflect community realities. CHWs' scope of work is varied and may change over time, requiring ongoing training. The modular, local and mix of practical and classroom training approach worked well, helping to address gender and literacy challenges and developing a supportive cohort of CHWs. A package of supervision, community support, regular provision of supplies, performance rewards and regular remuneration is vital to retention and performance of CHWs. But there are challenges with supervision, scarcity of supplies, inadequate community recognition and unfulfilled promises about allowances. Clear communication about incentives with facility staff and communities is required as is their timely delivery. Conclusions This is the first study that has explored the management of CHWs in fragile settings. CHWs' interface role between communities and health systems is critical because of their embedded positionality and the trusting relationships they (often) have. Their challenges are aligned to those generally faced by CHWs but chronic fragility exacerbates them and requires innovative problem solving to ensure that countries and communities are not left behind in reforming the way that CHWs are supported.